Listening to the stories of women in the South African rural water services sector to understand how their traditional roles intersect with government gender mainstreaming initiatives - Hanise, Bantu Edgar (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--Stellenbosch University, 2008.